Implementation of the Halal Ecosystem in Bangkalan Regency from a Maqashid Syariah Perspective - Khoirun Nasik; Ahmad Musadad; Firman Setiawan (Universitas Darussalam Gontor, 2024)
**English**This research is motivated by the fact that the development of the halal ecosystem is still not optimal in Bangkalan, Madura. Reading the implementation of the halal ecosystem according to the theory of ushul fiqh in the form of maqashid al-syariah is a new basis for measuring implementation, in line with the objectives of Islamic law. This research aims to analyze the implementation of halal ecosystem in Bangkalan Regency, using the maqashid al-syariah theory approach. The research method used is a type of qualitative descriptive research with an ushul fiqh approach in the form of the maqashid al-Syariah method. Data analysis was carried out using an inductive method. The research results show that although Bangkalan Regency has great potential in the halal industry, the development of the halal ecosystem still faces several obstacles. These obstacles include, among other things, aspects of facilities, infrastructure and policy. Meanwhile, the HR aspect can be resolved by collaborating with the UTM halal center. The integration of religious tourism in the ecosystem also contributes positively to accelerating the development of the halal industrial ecosystem in Bangkalan Regency. High tourist visits to religious tourist attractions will increase demand for halal products and services, which will definitely increase production levels and employment. As for the analysis from the maqashid al-syariah perspective, it can be explained that the development of the halal ecosystem in Bangkalan district is generally in line with the five dimensions of maqashid. However, there are several things that are considered not optimal, namely in the hifdz al-nafs dimension, namely the limited number of halal-certified products and the absence of health services at tourist attractions for visitors, the hifdz al-'aql dimension, namely the lack of clear information regarding guides prepared by the local government to support the implementation of tourism, and the dimension of hifdz al-mal, namely limited digital infrastructure and the lack of optimal integration and interconnection of Islamic philanthropic institutions in the halal industrial ecosystem. **Indonesia**Penelitian ini dilatarbelakangi oleh adanya pengembangan ekosistem halal yang masih belum optimal di wilayah Bangkalan, Madura. Pembacaan implementasi ekosistem halal menurut teori ushul fiqh, maqashid al-syariah merupakan pijakan baru dalam mengukur suatu implemetasi yang selaras dengan tujuan-tujuan dalam syariat Islam. Penelitian ini bertujuan untuk menganalisis implementasi ekosistem halal di Kabupaten Bangkalan dengan pendekatan teori maqashid al-syariah. Metode penelitian yang digunakanan adalah deskriptif kualitatif dengan pendekatan ilmu ushul fiqih berupa metode maqashid al-Syariah. Analisis data dilakukan dengan metode induktif. Hasil penelitian menunjukkan bahwa Kabupaten Bangkalan memiliki potensi yang besar dalam industri halal, namun pengembangan ekosistem halal masih menghadapi beberapa kendala. Kendala tersebut antara lain berkaitan dengan aspek sarana, infrastruktur, dan kebijakan. Sedangkan pada aspek SDM bisa teratasi dengan kerja sama dengan halal center UTM. Integrasi pariwisata religi dalam ekosistem juga berkontribusi positif dalam rangka percepatan pengembangan ekosistem industri halal di Kabupaten Bangkalan. Tingginya kunjungan wisatawan pada objek wisata religi akan menaikkan permintaan terhadap produk dan layanan halal, yang secara pasti akan menaikkan tingkat produksi dan penyerapan tenaga kerja. Adapun analisis dalam perspektif maqashid al-syariah dapat dijelaskan bahwa pengembangan ekosistem halal di kabupaten Bangkalan secara umum sudah sejalan dengan lima dimensi maqashid. Namun, ada beberapa hal yang dianggap belum optimal, yaitu pada dimensi hifdz al-nafs yakni terbatasnya produk yang bersertifikasi halal dan tidak adanya layanan kesehatan di objek wisata bagi pengunjung, dimensi hifdz al-‘aql yakni belum jelasnya informasi terkait pemandu yang disiapkan oleh pemerintah daerah untuk mendukung penyelenggaraan pariwisata, dan dimensi hifdz al-mal yakni terbatasnya infrastruktur digital serta belum optimalnya integrasi dan interkoneksi lembaga filantropi Islam dalam ekosistem industri halal.